Circular and square slender concrete-filled tubular columns under large eccentricities and fire. (July 2015) - Espinos, A.; Romero, M.L.; Serra, E.; Hospitaler, A.
Abstract: Previous investigations have revealed the unsafety of the current calculation methods in Eurocode 4 for evaluating the fire resistance of concrete-filled steel tubular (CFST) columns, which has given place to a movement in Europe for correcting the existing methods and developing new design rules. In order to support the development of new guidance, further experimental research is needed, especially concerning slender columns and large eccentricities. In this paper, the results of a series of fire tests on slender CFST columns of different section shape (circular and square) subjected to large eccentricities are presented. The influence of the cross-section shape, load eccentricity and percentage of reinforcement on the response of these columns at elevated temperatures is studied in this paper, focusing on the effect of large eccentricities combined with high slenderness. On the basis of the experimental results, the current design rules in Eurocode 4 are assessed, and a previous calculation method developed by the authors is also evaluated. Highlights: Fire tests on circular and square slender concrete filled tubular columns. The effect of large eccentricities combined with high slenderness is investigated. The current design rules in Eurocode 4 Part 1.2 are assessed. A new calculation method developed by the authors is evaluated.